Weight-adjusted-waist index is associated with increased risk of sleep disturbances in the U.S. adult population: an analysis of NHANES 2007–2012 - Haiping Xie; Chuhui Chen; Ting Li; Lizhen Xu; Jixing Liang; Junping Wen; Gang Chen; Liangchun Cai (Eating and Weight Disorders)
Abstract Objective The weight-adjusted-waist index (WWI) is a novel measure of central adiposity, potentially linked to various sleep disturbances. This study explores the relationship between WWI and sleep outcomes, such as trouble sleeping, sleep disorder, and sleep duration. Methods Data from the National Health and Nutrition Examination Survey 2007–2012 were analyzed, including 13,494 participants. The analysis focused on individuals aged 20 years and older who provided information on WWI and sleep. Sleep status was determined based on responses to the following questions: (1) “How many hours do you sleep?”; (2) if they reported trouble sleeping; and (3) if they had physician-diagnosed sleep disorders. Regression models assessed the association between WWI and sleep outcomes across the entire population and within subgroups. Restricted cubic spline (RCS) analysis was conducted to examine potential non-linear relationships between WWI and sleep outcomes. Results A higher WWI was significantly correlated with an increased likelihood of trouble sleeping (OR = 1.26, 95% CI: 1.16, 1.36; p < 0.001) and sleep disorder (OR = 1.71, 95% CI: 1.50, 1.95; p < 0.001) in the overall population. RCS analysis indicated a linear relationship between WWI and these sleep outcomes. Subgroup analysis identified that the connection between WWI and trouble sleeping was most pronounced among Non-Hispanic Blacks and individuals with lower educational levels. For sleep disorder, the association was stronger in males and Non-Hispanic Blacks. A slight negative association between WWI and sleep duration was found, especially among non-drinkers (β = − 0.13, 95% CI: − 0.24, − 0.02; p = 0.028). Conclusion The findings highlight a significant and linear relationship between elevated WWI and an increased likelihood of experiencing trouble sleeping and sleep disorder, with variations observed across different demographic and lifestyle subgroups. These results imply that central adiposity, as measured by WWI, plays an important role in sleep health. Level of evidence Level III: Evidence obtained from well-designed cohort or case–control analytic studies.